ADS024, a Bacillus velezensis strain, protects human colonic epithelial cells against C. difficile toxin-mediated apoptosis - Xie, Ying; Chupina Estrada, Andrea; Nelson, Becca; Feng, Hanping; Pothoulakis, Charalabos; Chesnel, Laurent; Koon, Hon Wai (Frontiers in Microbiology, 2023)
Clostridioides difficile infection (CDI) causes intestinal injury. Toxin A and toxin B cause intestinal injury by inducing colonic epithelial cell apoptosis. ADS024 is a Bacillus velezensis strain in development as a single-strain live biotherapeutic product (SS-LBP) to prevent the recurrence of CDI following the completion of standard antibiotic treatment. We evaluated the protective effects of the sterile filtrate and ethyl acetate extract of conditioned media from ADS024 and DSM7 (control strain) against mucosal epithelial injury in toxin-treated human colonic tissues and apoptosis in toxin-treated human colonic epithelial cells. Ethyl acetate extracts were generated from conditioned culture media from DSM7 and ADS024. Toxin A and toxin B exposure caused epithelial injury in fresh human colonic explants. The sterile filtrate of ADS024, but not DSM7, prevented toxin B-mediated epithelial injury in fresh human colonic explants. Both sterile filtrate and ethyl acetate extract of ADS024 prevented toxin-mediated apoptosis in human colonic epithelial cells. The anti-apoptotic effects of ADS024 filtrate and ethyl acetate extract were dependent on the inhibition of caspase 3 cleavage. The sterile filtrate, but not ethyl acetate extract, of ADS024 partially degraded toxin B. ADS024 inhibits toxin B-mediated apoptosis in human colonic epithelial cells and colonic explants.